EKSPLORASI TEKNIK LEKAPAN PADA BUSANA PESTA DENGAN SUMBER IDE RUMAH BOLON DAN BUNGA ANGGREK TIEN - Dita Bella; Winwin Wiana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
Indonesia is known as a country with abundant wealth, including the wealth of traditional houses and flora. Traditional houses and flora are part of the natural wealth and culture of Indonesia, including a system of tools and living equipment and technology. The traditional house of Bolon is a work of cultural heritage that still exists today, as a residence for kings and has a philosophy and noble meaning contained in every corner of the building. Tien orchid (Cymbidium hartinahianium) is an endemic plant of North Sumatera,which lives in groups and was first discovered in 1976. As a source of archipelago ideas from the North Sumatera region, the traditional house of Bolon and the Tien Orchid flower can represent a symbol of the natural and cultural wealth of the people of North Sumatera, is one of the largest provinces in Indonesia. The curved design of the party dress that will be made is inspired by the shape of Bolon traditional house and Tien Orchid flower. The materials used for the curls are Ulos Sadum woven cloth, embroidery threand, pearls, and organza ribbon flowers. The method used is Project Based Learning (PBL). The result of this exploration study are aimed at preserving Indonesia’s natural and cultural wealth which is starting to become extinct and forgetten, through making a amatching and beautiful party dress. Key words: Lekapan technique, Rumah Bolon, Tien Orchid